Wykonaj działania, doprowadź je do najprostszej postaci:

1. -5(-3x+2+y)=

2. 3(a-b)=

3. -2(a+2b)=

4. 7(-x+5)=

5. 2x(6+4x2-5x)=

6. -4(-3a-4b-5c)=

7. -x(2a+4ab+3ax)=

8. -3(3-2ab+5b)=

9. 3a2(b-a)=

10. 5m(4+5p-2q)=

11. -4x(-5x+5xy-3y)=

12. 2x(3xy+5x2+6x3)=

13. -4a(-5+4a2+3ab2)=

14. 2m(m+2mn+3n)=

15. -4(a-5b)=

16. -3(-2b-a)=

17. -x(z-y)=

18. 10x(-y+1)=

19. -y(5x3y2+3x-2yz)=

20. a2(-a+3ab+6b)=

21. 2(x-y)-3(4y-2x)=

22. -(a+2b-4c)+2(-3a+4b-2c)=

23. m(m+3n)+4n(m+3n)=

24. -4(a-5b)-3(-2b-a)=

25. -x(z-y)-z(-x+y)=

26. -5x(2-y)-y(5x+1)+10x(-y+1)=

27. 2x2(x+2y)+7x(3x2-5y)=

28. -3(2p-4r+6pr)+2(p+3r-2pr)=

29. (8a-10b):(-2)=

30. (5x-20):5=

31. (4+12x+8y):4=

32. (3+6a-9b):(-3)=

33. (-6m+9n-12mn):6=


Odpowiedź :

Odpowiedź: Mam nadzieję, że pomogłam :)

1. -5(-3x+2+y)= 15x-5y-10

2. 3(a-b)= 3a-3b

3. -2(a+2b)= -2a-4b

4. 7(-x+5)= -7x+35

5. 2x(6+4x2-5x)= 8[tex]x^{3}[/tex]-10[tex]x^{2}[/tex]+12x

6. -4(-3a-4b-5c)= 12a + 16b + 20c

7. -x(2a+4ab+3ax)= -3a[tex]x^{2}[/tex]- 2ax -4abx

8. -3(3-2ab+5b)= -15b + 6ab - 9

9. 3a2(b-a)= 3[tex]a^{2}[/tex]b -3[tex]a^{3}[/tex]

10. 5m(4+5p-2q)= 20m +25mp - 10mq

11. -4x(-5x+5xy-3y)= 20[tex]x^{2}[/tex]-20[tex]x^{2}[/tex]y + 12xy

12. 2x(3xy+5x2+6x3)= 6[tex]x^{2}[/tex]y+10[tex]x^{3}[/tex]+12[tex]x^{4}[/tex]

13. -4a(-5+4a2+3ab2)= -16[tex]a^{3}[/tex]-12[tex]a^{2}[/tex][tex]b^{2}[/tex]+ 20a

14. 2m(m+2mn+3n)= 2[tex]m^{2}[/tex]+ 4[tex]m^{2}[/tex]n + 6mn

15. -4(a-5b)= -4a+20b

16. -3(-2b-a)= 3a+6b

17. -x(z-y)= -xz+xy

18. 10x(-y+1)= -10xy + 10x

19. -y(5x3y2+3x-2yz)= -5[tex]x^{3}[/tex][tex]y^{3}[/tex]-3xy +2 [tex]y^{2}[/tex]z

20. a2(-a+3ab+6b)= [tex]a^{3}[/tex]+ 3[tex]a^{3}[/tex]b+6[tex]a^{2}[/tex]b

21. 2(x-y)-3(4y-2x)= 2x-2y -12y+6x=8x-14y

22. -(a+2b-4c)+2(-3a+4b-2c)= -a-2b+4c-6a+8b-4c= -7a+6b

23. m(m+3n)+4n(m+3n)= [tex]m^{2}[/tex]+3mn + 4mn + 12[tex]n^{2}[/tex]= [tex]m^{2}[/tex] + 7mn + 12[tex]n^{2}[/tex]

24. -4(a-5b)-3(-2b-a)= -4a+20b+6b+3a= -a+26b

25. -x(z-y)-z(-x+y)= -xz+xy +xz- yz= xy-yz

26. -5x(2-y)-y(5x+1)+10x(-y+1)= -10x+5xy-5xy-y-10xy+10x= -10xy-y

27. 2x2(x+2y)+7x(3x2-5y)= 2[tex]x^{3}[/tex]+4 [tex]x^{2}[/tex]y+ 21[tex]x^{3}[/tex]-35xy

28. -3(2p-4r+6pr)+2(p+3r-2pr)= -6p+12r-18pr +2p+6r-4pr= -4p+18r-22pr

29. (8a-10b):(-2)= -4a+5b

30. (5x-20):5= x-4

31. (4+12x+8y):4= 1+3x+2y

32. (3+6a-9b):(-3)= -1-2a+3b

33. (-6m+9n-12mn):6= -1+[tex]\frac{3}{2}[/tex] n-2mn